2019
DOI: 10.1371/journal.pone.0210775
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors for wearing personal protective equipment (PPE) in a health care environment evaluated in a randomised study

Abstract: Pandemics and re-emerging diseases put pressure on the health care system to prepare for patient care and sample logistics requiring enhanced personnel protective equipment (PPE) for health care workers. We generated quantifiable data on ergonomics of PPE applicable in a health care setting by defining error rates and physically limiting factors due to PPE-induced restrictions. Nineteen study volunteers tested randomly allocated head- or full body-ventilated PPE suits equipped with powered-air-purifying-respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 22 publications
5
101
1
1
Order By: Relevance
“…On the other hand, although employing strict biosecurity measures is a must to prevent spread of infection to self and others, it was a significant stressor for nurses of ZFH. This is consistent with Loibner et al (2019) who reported that reduced dexterity due to multiple glove layers, impaired visibility by flexible face shields and back pain related to the respirator of the fully ventilated suit, heat stress, and liquid loss were perceived as strong stressors especially at high working temperature. Other significant COVID-19-associated stressors for nurses in both ZFH and ZGH were the personal fears of being isolated, transmitting the disease to families or friends, the unknown duration of the epidemic, lack of treatment for the disease, news of new cases of COVID-19 reported in TV/newspaper, and predictable shortages of staff, supplies, and adequate protective measures.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, although employing strict biosecurity measures is a must to prevent spread of infection to self and others, it was a significant stressor for nurses of ZFH. This is consistent with Loibner et al (2019) who reported that reduced dexterity due to multiple glove layers, impaired visibility by flexible face shields and back pain related to the respirator of the fully ventilated suit, heat stress, and liquid loss were perceived as strong stressors especially at high working temperature. Other significant COVID-19-associated stressors for nurses in both ZFH and ZGH were the personal fears of being isolated, transmitting the disease to families or friends, the unknown duration of the epidemic, lack of treatment for the disease, news of new cases of COVID-19 reported in TV/newspaper, and predictable shortages of staff, supplies, and adequate protective measures.…”
Section: Discussionsupporting
confidence: 90%
“…Pictures of HCWs' faces bruised by wearing masks for extended periods have been used to illustrate the extreme work conditions when caring for such patients. While pain, heat stress and fluid loss with using Powered Air-Purifying Respirators (PAPR) were predicted by experimental data [14], there are no real-life reports of this issue when using PPE that is available to HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…An international study reported that when nurses wear personal protective equipment (PPE), they usually take 4-6 working hours without a break. This is very critical to nurses' well-being, since longer hours wearing PPE can cause fatigue, stress, and exhaustion, making healthcare providers prone to causing medical errors [26]. Hence, nursing administration should organize staffing and scheduling to avoid mental and physical health impairment.…”
Section: Discussionmentioning
confidence: 99%